Solvation of Coumarin 480 within nano-confining environments: Structure and dynamics - Elola, Maria Dolores (2014)
Equilibrium and dynamical characteristics pertaining to the solvation of the fluorescent probe Coumarin 480 within different confining environments are investigated using molecular dynamics simulations. Three kinds of confining systems are examined: (i) the cetyltrimethylammonium bromide (CTAB)/isooctane/1-hexanol/water; cationic inverse micelle (IM) (ii) a CTAB/water direct micelle (DM), and (iii) a silica-surfactant nanocomposite, comprising a cylindrical silica pore (SP) containing small amounts of water and CTAB species adsorbed at the pore walls. The solvation structures in the three environments differ at a qualitative level: an exchange between bulk- and interface-like solvation states was found in the IM, whereas in the DM, the solvation states of the probe are characterized by its embedding at the interface, trapped among the surfactant heads and tails. Within the SP structure, the coumarin exhibits alternations between internal and interfacial solvation states that occur on a ∼20 ns time scale and operate via 90° rotations of its molecular plane. The solvation responses of the environment following a vertical excitation of the probe are also investigated. Solvation times resulted between 2 and 1000 times longer than those found in bulk water, with a fast-to-slow trend IM→DM→SP, which can be interpreted in terms of the solvation structures that prevail in each case.